Socialization regarding the legality and distribution permits for food products UMKM in Batujajar Transit Apartment, West Bandung Regency - Putri Widyanti Harlina; Elazmanawati Lembong; Endah Wulandari; Adhi Prapaskah Hartadi (Universitas Muhammadiyah Magelang, 2025)
In the business world, especially in Micro, Small, and Medium Enterprises (MSMEs), business legality and distribution permits are crucial aspects. Business legality refers to the legal status of a business, while a distribution permit is an official approval from the government to market a product or service. Both not only fulfill legal administrative requirements but also provide benefits and protection to business actors. The purpose of this community service is to socialize the importance of business legality and distribution permits for MSME food products to participants at the Batujajar Transit Apartment in West Bandung Regency. The methods used include lectures, discussions, and socialization related to both aspects. This activity succeeded in increasing participants' understanding of the importance of business legality and distribution permits. This increase is reflected in the positive feedback from participants, who actively asked about the permit processing process and expressed their intention to ensure business legality before launching a product. At the end of the activity, partners showed increased concern for business legality, which is expected to provide protection when marketing products and enhance public trust, allowing MSME businesses to develop further.